INTERACTIVE TECHNICAL EDUCATION - HRUBÝ, Peter (Trends in education, 2013)
The school subject technic is used in elementary schools as a first contact with the technique, and also as a motivation for further study at secondary schools in the technical field. Subject as such is mainly expressed combining teaching theoretical information and practical skills practicing. After school reform, in which the teaching of the subject seriously limited, the subject is taught in many schools only theoretically. The use of interactive teaching aids can contribute to better outcomes of students in this subject.
Keywords: the school subject technic; interactive whiteboards; interactive teaching aids; lesson phase